Nixon, Kissinger and the Shah: US-Iran relations and the Cold War, 1969-1976 - Alvandi, R (2011)
This thesis examines the nature and dynamics of U.S.-Iran relations during the Cold War under the leadership of U.S. President Richard Nixon, his adviser Henry Kissinger, and Shah Mohammad Reza Pahlavi of Iran. This revisionist account critically examines the popular view of Mohammad Reza Shah as a mere instrument of American strategies of containment during the Cold War. Relying on recently declassified American documents, British government papers, and the diaries, memoirs and oral histories of Iranian actors, this thesis restores agency to the shah as an autonomous Cold War actor and suggests that Iran evolved from a client to a partner of the United States under the Nixon Doctrine. This partnership was forged during Nixon’s first term in office between 1969 and 1972, as the United States embraced a policy of Iranian primacy in the Persian Gulf region. Thanks to a long-standing friendship with the president, the shah was able to exercise extraordinary influence in the Nixon White House. This partnership reached its peak during Nixon’s second term as the United States supported Iran’s regional primacy against the challenge from Iraq. The shah drew Nixon and Kissinger into Iran’s secret war against Iraq in Kurdistan in 1972, by portraying Iran’s long-standing regional conflict with Iraq as a Cold War confrontation with the Soviet-backed Ba’th regime in Baghdad. When the shah unilaterally decided to abandon the Kurds in a deal with Iraq’s Saddam Hussein in 1975, Kissinger had little choice but to acquiesce, despite the personal embarrassment and domestic recriminations that followed. The U.S.-Iran partnership declined following Watergate and Nixon’s resignation in 1974. In spite of the best efforts of the shah and Kissinger, between 1974 and 1976 the United States and Iran were unable to reach an agreement on U.S. nuclear exports to Iran. President Gerald Ford tried to impose a discriminatory nuclear agreement on Iran that was rejected by the shah because it violated Iran’s national sovereignty. Under Ford, the United States reverted to treating Iran as a client rather a partner of the United States.